Late Adolescent Development and Its Implications for Education - Yeni Yeldia Nopita Sari; Ermis Suryana; Zulhijra Zulhijra (FKIP - Universitas Riau, 2026)
Late adolescence (ages 18-25 years) is a critical transitional phase toward adulthood, marked by maturity in physical, intellectual, emotional, social, moral, and religious dimensions, yet frequently challenged by emotional instability, declining learning motivation, and risks of moral degradation due to peer pressure and digital influences. This study aims to holistically examine late adolescent development and its implications for education within the Indonesian context.Employing a qualitative approach through systematic literature review, the study analyzes classical theories (Piaget, Erikson) and recent empirical research on biological maturation and Islamic religious education. Findings reveal that emotional maturity is a key factor in academic and social success, with Islamic religious education providing a moral framework for emotion regulation through values such as patience, empathy, and tawakal, thereby preventing aggression, depression, and juvenile delinquency.Educational implications include systemic reforms that promote adolescent autonomy via collaborative extracurricular programs, counseling, inclusive character education rooted in local culture, and active involvement of parents and teachers. The study concludes that a holistic Islamic religious education approach effectively optimizes the multidimensional potential of late adolescents, ensures successful transition to adulthood, and offers practical recommendations for educators and policymakers.